Model Collaborative Governance untuk Mitigasi Bencana Hidrometeorologi di Deli Serdang - Donny Alviandi; Ernalem Bangun; Arifuddin Uksan (Universitas Negeri Gorontalo, 2025)
Deli Serdang Regency is one of the regions with a high level of vulnerability to hydrometeorological disasters such as flooding, tornadoes, and coastal abrasion. The complexity of its geographical characteristics, settlement expansion, and changes in land use require a collaborative approach to disaster governance. This study aims to analyze the implementation of Collaborative Governance in hydrometeorological disaster mitigation using the Ansell Gash model as the analytical framework. The research employs a qualitative-descriptive method through literature reviews, observations, and interviews with stakeholders at the regency and sub-district levels. The findings indicate that collaborative governance in Deli Serdang has been implemented in several aspects but remains suboptimal, particularly in the mitigation and preparedness phases. The study shows that the components of drivers, principled engagement, shared motivation, and capacity for joint action have not been fully internalized within the institutional structure of BPBD and its multi-stakeholder partners. This research offers recommendations to strengthen spatial-based collaborative governance and integrate geospatial data to enhance disaster mitigation efforts in Deli Serdang.